Anthimus and His Work, or on Aromatics and Wildfowl in De observatione ciborum [Antimus i jego dzieło, czyli o aromatach i dzikim ptactwie w “De observatione ciborum"] - Kokoszko, Maciej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The present study focuses on select fragments of De observatione ciborum only. It starts with Chapter 13 (describing preparation of hare), analysing exclusively the recipe for a sauce included therein as it illustrates accurately Anthimus’ world of knowledge, and gives an opportunity to supplement the list of ingredients of the delicacy. Subsequently, the analysis moves on to Chapters 25, and 26 of De observatione ciborum, which have some information on Anthimus’ medical practice and his creativity as a physician. The research is concluded with the contents of Chapter 33, which provide data on the place, where the work was composed.